Art Therapy Alleviates the Levels of Depression and Blood Glucose in Diabetic Patients: A Systematic Review and Meta-Analysis - Yang, Qingqi; Shao, Qunhui; Xu, Qiang; Shi, Hui; Li, Lin (Frontiers in Psychology, 2021)
Objective: To systematically analyze the effects of art therapy on alleviating the levels of depression, anxiety, and reducing blood glucose in patients with diabetes mellitus. Methods: We searched Cochrane Library, PubMed, Embase, and ClinicalTrials.gov databases from inception to April 28, 2020. The language of publication was limited to English. Randomized controlled trials (RCTs) that used art therapy to improve mental disorders in patients with diabetes mellitus were involved. After selection of eligible studies, data were extracted, including the first author’s full-name, year of publication, the first author’s country of residence, number of intervention groups and control groups, the mean age of participants, method of intervention, duration of follow-up, and outcome measures. Assessment of quality of included studies and data extraction were independently carried out by two researchers. RevMan 5.3 software was used to perform statistical analysis. Results: A total of 396 samples from 5 studies were included, and the included studies were all parallel RCTs. Methods of art therapy included music therapy and painting therapy. The results showed that compared with the control group, art therapy could positively affect the levels of depression (standardized mean difference (SMD), -1.36; 95% confidence interval (CI), (-1.63, -1.09); P < 0.00001) and blood glucose in patients with diabetes mellitus (mean difference (MD), -0.90; 95% CI, (-1.03, -0.77); P<0.0001), while it had no influence on the levels of anxiety (SMD, -0.31; 95% CI, (-0.93, 0.31); P=0.32) and glycated hemoglobin (MD, 0.02; 95% CI, (-0.42, 0.47); P=0.91). Conclusion: This meta-analysis indicated that art therapy may have beneficial effects on the levels of depression and blood glucose in patients with diabetes mellitus.